The applicability of the Pipe Model Theory in trees of Scots pine of Poland - T. Jelonek; W. Pazdrowski; M. Arasimowicz; A. Tomczak; R. Walkowiak; J. Szaban (Journal of Forest Science, 2008)
In order to test the application importance of the Pipe Model Theory and to develop models for the share of sapwood in tree stems, a total of 114 Scots pines (Pinus sylvestris L.) were felled within the natural range of this species in three natural positions located in northern and western Poland. The analyses were conducted on wood coming from trees from the main layer of the stand, i.e. the first three classes according to the classification developed by Kraft. Dependences were analyzed between the biometric characteristics of model trees, e.g. tree height, diameter at breast height, crown length, crown basal area and the area and volume of sapwood in the stem. All the analyzed characteristics, both biometric traits and sapwood characteristics, were found to be correlated significantly (P < 0.05) positively. Conducted analyses indicate that the postulates proposed in the Pipe Model Theory and Profile Theory require certain modifications and regression models developed for each social class of tree position in the stand for dependences of sapwood area and volume on the above mentioned biometric variables indirectly include changes occurring in time.